Epidemiology of Cryptococcosis and Cryptococcal Meningitis in a Large Retrospective Cohort of Patients After Solid Organ Transplantation. (12th January 2017) - George, Ige A.; Santos, Carlos A. Q.; Olsen, Margaret A.; Powderly, William G.
Abstract: Background: Cryptococcosis is the third most common invasive fungal infection in solid organ transplant (SOT) recipients. There are no nationally representative data describing the incidence, risk factors, and outcomes of cryptococcosis after SOT. Methods: We assembled a large cohort of adult SOT recipients using Classification of Diseases, Ninth Revision, Clinical Modification billing data from Healthcare Cost and Utilization Project State Inpatient Databases of Florida (2006–2012), New York (2006–2011), and California (2004–2010). Demographics, comorbidities, death, and cryptococcal infections coded during hospitalization were identified. Results: A total of 42634 adults with SOT were identified during the study period. Cryptococcal disease was identified in 0.37% (n = 158), 44% of which had meningitis (n = 69). Median time to diagnosis of cryptococcosis was 464 days (range, 4–2393). The median time to onset of cryptococcosis was earlier for lung (191 days; range, 7.5–1816), heart (195 days; range, 4–1061), and liver (200 days; range, 4–1581) compared with kidney transplant recipients (616 days; range, 12–2393; P < .001, log rank test). Very early-onset disease (<30 days after transplantation) more frequently occurred in liver and lung transplant recipients. Lung transplant recipients had the highest risk of cryptococcosis (hazard ratio [HR], 2.10; 95% confidence interval [CI], 1.21–3.60). Cryptococcosis was associated with death (HR, 2.29; 95% CI, 1.68–3.11), after adjusting for age, type of SOT, and other comorbidities. Conclusions: Cryptococcosis is rare after SOT, but it is associated with significantly increased risk of death. Lung transplant recipients are at highest risk for cryptococcosis among SOTs. Nonkidney transplants have earlier onset of cryptococcosis and higher risk of death compared with kidney transplant recipients.